Bibliotherapy- Use of books for healing: an Experiential Study to Introduce Prospective Bibliotherapy Service in Libraries - Nazi, Rummana; Ali, P. M. Naushad; Akhouri, Deoshree (Journal of Information and Knowledge, 2023)
Since ancient times, books have been utilized as a therapeutic aid. However, its function and mode of operation have surely changed over time. It is the field of study that examines how writing might be used and how it might affect people's lives. Under the direction of a trained assistant, it is an act of interactive interplay between the reader's personality and the literature. People have various mental health issues, challenges, and difficulties in recent years. Bibliotherapy is a concept where, with the help of books, people manage their lives and their challenges. This study aims to see the efficacy of bibliotherapy in patients with obsessive-compulsive disorder (OCD) and depression. Based on this experiment, researchers propose a conceptual framework for libraries. A book by Catherine M. Pittman titled "Rewire Your OCD Brain: Neuroscience-Based Skills to Break Free from Obsessive Thoughts and Fears" served as the primary data gathering tool for this research, which was carried out using an experimental methodology. The study's findings demonstrate a substantial difference between the experimental and wait-list groups in the treatment of mild to moderate OCD and depression symptoms with the application of bibliotherapy. Based on the findings, a conceptual framework with some recommendations has been suggested.